Optical properties of thin discontinuous metal films - N. Stefanou; A. Modinos (Journal of Physics: Condensed Matter, 1991)
The authors present numerical calculations of the absorbance of light by a plane of metallic spheres. The absorbance is calculated as a function of frequency for s- and p-polarized light, for different angles of incidence and for different coverages. They demonstrate the importance of l-pole terms beyond the dipole (l=1) term in interparticle scattering. They examine the effect of disorder and consider the influence of a dielectric substrate on the absorbance of the system consisting of a substrate plus adsorbed spheres.